Model Pembelajaran Konstruktivisme Terhadap Hasil Belajar Bahasa Inggris Pada Siswa Kelas 7 di MTS Bale Da’wah Nabawi - Iswandi, Taufan; Z, Zohrani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study was to determine how the constructivism learning model impacts on students' English learning outcomes in Class 7 of MTs Bale Da'wah Nabawi in Pohgading, East Lombok. Most of the learning models are based on the old teaching approach, namely lectures and assignments. As a result, students become passive and accept what is given by the teacher. In addition, students are not enthusiastic during the learning process and prefer to be silent, so that communication only goes one way. Therefore, the researcher tried to use the Constructivism Learning Model to solve this problem. This experimental study is a research. Students in class 7A were used as an experimental group with 27 students and students in class 7B were used as a control group with 27 students. After the data were collected and processed, the researcher found an average value of 82.40 for the experimental group and 66.85 for the control group. in hypothesis testing, the researcher used the t-test formula. The researcher found a t-test value of 6.015 and a t-table at a significance level of 5% of 1.684, so the hypothesis was accepted. This means that there is an influence of the Constructivism Learning Model on English Learning Outcomes in Students in Grade 7 at MTs Bale Da'wah Nabawi.